Forgiveness Therapy in Islamic Psychology Perspective: Healing the Inner Child Parenting Wounds - Fadilah, Risydah; Parinduri , Sari Atika; Nurhayani; Parinduri, Sari Atika (Psikis : Jurnal Psikologi Islami, 2024)
This study was conducted to see a decrease in the inner child parenting wounds by giving forgiveness theraphy. The subjects of the study were 24 adolescents who participated in the forgiveness training after filling out a questionnaire and their scores were taken as research subjects. The method used was a quasi-experimental one group pretest-posttest design with two measurements, namely before the intervention, and after the forgiveness training intervention. The study was conducted by using the forgiveness theraphy, appreciation of the inner child. The average pretest and posttest scores: the pretest score 271, 47 and the posttest was 164, 42. There was a difference of 91, 47, where the average posttest value was higher than the pretest value. The results of the One-Sample Kolmogorov-Smirnov Test analysis showed a significant value of 0.000 < 0.05., where the significant value < 0.05 means that HO was rejected and HA was accepted. The results of this study concluded that there was a decrease in the level of inner child parenting wounds after participating in forgiveness theraphy.